(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Timely diagnosis and treatment of biliary sludge provides ample opportunities for primary and secondary prevention of cholelithiasis and reduces the number of surgical interventions. Our study examined 100 pregnant women with biliary sludge. The effect of the drug "Xophytol" artichoke extract (France / Rosa-Phytopharma) on the state of the gallbladder and fetoplacental blood flow was studied. The study was conducted in the multidisciplinary clinic of TMA during 2021-2024, the anamnesis of patients admitted for inpatient treatment was studied. Analysis of the obtained data showed a positive effect of the drug on the regression of biliary sludge and the state of fetoplacental blood flow.